2018
DOI: 10.1155/2018/4757893
|View full text |Cite
|
Sign up to set email alerts
|

Honey and Diabetes: The Importance of Natural Simple Sugars in Diet for Preventing and Treating Different Type of Diabetes

Abstract: Diabetes is a metabolic disorder with multifactorial and heterogeneous etiologies. Two types of diabetes are common among humans: type 1 diabetes that occurs when the immune system attacks and destroys insulin and type 2 diabetes, the most common form, that may be caused by several factors, the most important being lifestyle, but also may be determined by different genes. Honey was used in folk medicine for a long time, but the health benefits were explained in the last decades, when the scientific world was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 98 publications
5
68
0
5
Order By: Relevance
“…It is widely used as a nutrient supplementation Evidence-Based Complementary and Alternative Medicine and in traditional medicine. Since the last two decades, honey has been explored for its gastroprotective, hepatoprotective, reproductive, hypoglycemic, antioxidant, antihypertensive, antibacterial, antifungal, anti-inflammatory, immunomodulatory, wound healing, cardioprotective, and antitumor effects [33][34][35][36][37][38][39][40]. In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46].…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…It is widely used as a nutrient supplementation Evidence-Based Complementary and Alternative Medicine and in traditional medicine. Since the last two decades, honey has been explored for its gastroprotective, hepatoprotective, reproductive, hypoglycemic, antioxidant, antihypertensive, antibacterial, antifungal, anti-inflammatory, immunomodulatory, wound healing, cardioprotective, and antitumor effects [33][34][35][36][37][38][39][40]. In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46].…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…14 Inverted sugar syrup contains high amounts of Fructose; and several studies have shown that the anti-diabetic and hypoglacaemic effect of honey resulted from the Fructose component; owing to the fact that Fructose increase the uptake of hepatic Glucose as well as storage and synthesis of glycogen. 14,39,[40][41][42] It has been recently reported that Fructose has the ability to lower the blood Glucose in animals' models of diabetes; and the mechanisms involved in this process include prolongation of gastric emptying time and reduced rate of intestinal absorption, stimulation of glucokinase in the hypatocytes which plays an important role in the uptake and storage of Glucose as glycogen by the liver under the adipose tissues of the body. 14 Although, there are some studies that reported contrary opinions regarding the use of honey in the control and management of diabetes mellitus diseases, other several research findings favourably discuss and opined that honey with high amounts of Fructose can be used to manage and control Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…14,39,[40][41][42] It has been recently reported that Fructose has the ability to lower the blood Glucose in animals' models of diabetes; and the mechanisms involved in this process include prolongation of gastric emptying time and reduced rate of intestinal absorption, stimulation of glucokinase in the hypatocytes which plays an important role in the uptake and storage of Glucose as glycogen by the liver under the adipose tissues of the body. 14 Although, there are some studies that reported contrary opinions regarding the use of honey in the control and management of diabetes mellitus diseases, other several research findings favourably discuss and opined that honey with high amounts of Fructose can be used to manage and control Type 2 diabetes. Hence, the need for larger sample sized; multi-centre clinical controlled studies so that better and reliable conclusion can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…This for, honey consumption has potential health benefits due to the antioxidant and antimicrobial properties of honey [34]. Honey contains more than 200 components, with fructose, glucose, and water as main substances [35]. The antioxidant activity depends on the floral source, as well as on seasonal and environmental factors and the processing may also have effect on composition and antioxidant activity of honey [36].…”
Section: Nutritional Antimicrobial and Functional Properties Of Honeymentioning
confidence: 99%